Diagnostic performance between histopathological and molecular methods in the detection of Helicobacter pylori - Lucas Luiz L. Silva; Igor M. C. Calassa; Ana Karoline S. Oliveira; Amanda F. P. L. Ramos; Jaqueline C. Pontes; Daniela M. M. Cardoso; Lucas T. Rasmussem; Lilian Carla Carneiro; Monica S. Barbosa (Sociedade Brasileira de Patologia Clínica, 2021)
ABSTRACT Introduction: Helicobacter pylori (H. pylori) is a Gram negative bacterium considered to be the etiologic agent of various gastric diseases. The prevalence of bacterial infection varies according to age, geographic location, ethnicity and socioeconomic status. The chronic infection caused by microorganism can favor the development of severe pathologies such as gastric adenocarcinoma. In this sense, early diagnosis is essential for a better prognosis and therapeutic success. Several diagnostic methods performed using invasive and non-invasive techniques, with different sensitivity and specificity, have been used in the detection of H. pylori. Objective: To compare the performance of the molecular and histopathological technique used in the diagnosis of H. pylori infection. Methods: 76 gastric tissue samples were collected from dyspeptic patients who underwent molecular and histopathological diagnosis. Molecular detection was performed using the ribosomal gene (16S rRNA) using the polymerase chain reaction (PCR) technique. Results: The PCR-based molecular diagnostic method detected the bacterium in 63.1% of the samples, while the histopathological test identified the microorganism in only 38.1% of gastric biopsies. The data demonstrated that the PCR technique was about 1.6 times more sensitive than the histopathological technique. Conclusion: The PCR technique was the most efficient diagnostic method for detecting H. pylori and can be implemented in the laboratory routine as a complementary test for the early detection of H. pylori.